(3GdLOjO aj GdJehjd GdeUQajs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2002)
(3GdJehjd GdJCLjQj(B- (3TQGA Mbhb GdJLGQjI(B- (3GdVeGf GdeUQaj(B- (3eLGdGJ LOjOI ddEFJeGf GdeUQaj(B.s
Keywords: (3GdHfhc(B- (3bhGfjf hJTQjYGJ(B- (3eUQ s; (3GdJehjds; (3GdeUGQas